Membangun Demokrasi Partisipatif Mahasiswa Program Studi Manajemen Universitas PGRI Adi Buana Surabaya Untuk Menjaga Keseimbangan Hak Dan Kewajiban - Sean Nabilah Apsarini; Balqis Khairunisa Frisyanto; Putri Salsabilah; Suyono (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2025)
Rights and obligations are two important elements that complement each other in student life as part of the academic community. This research aims to explore how students of the Management Study Program of PGRI Adi Buana University Surabaya understand and apply the balance between their rights and obligations, especially in the context of participatory democracy in the campus environment. This study uses a descriptive qualitative approach with data collection methods through interviews, documentation, and literature analysis. The results show that although students understand the importance of balancing rights, such as freedom of opinion and the right to education, with obligations such as learning and obeying campus rules, their participation in campus democracy is still relatively low. The main factors that affect this include lack of socialization, weak motivation, and limited time. These findings underscore the need for an integrated strategy to increase students' awareness of the importance of balancing rights and obligations, as well as encourage their active participation in campus democracy. The implication of this research is the importance of forming an academic culture that supports active student involvement to create a democratic, harmonious, and inclusive campus environment.